The effect of interventional program underpinned by health belief model on awareness, attitude, and performance of nurses in preventing nosocomial infections: A randomized controlled trial study - Hosseinpour, Mahmoud; Eslami Akbar, Rasool; Faseleh Jahromi, Mohsen; Badiyepeymaiejahromi, Zohreh (Investigación y Educación en Enfermería, 2024)
Objective. The present study examined the effect of an interventional program underpinned by the Health Belief Model (HBM) on nurses’ awareness, attitude, and performance in preventing nosocomial infections. Methods. This randomized controlled trial study was performed on 60 clinical nurses in lar, Iran. Nurses were selected using the simple random sampling method and assigned to two experimental (n=30) and control (n=30) groups. Data collection tool included the valid and reliable questionnaire was developed by Soleimani et al. The research intervention consisted of five 90-min sessions based on the health belief model in preventing hospital infection for experimental group. Before the intervention, immediately and two months after the intervention, the two groups completed the questionnaire. The control group received no intervention. Results. Data analysis showed that the differences between the two groups was statistically significant immediately and two months after the intervention (p<0.05). In experimental group the changes in the mean score of knowledge, attitude and performance of nurses before, immediately and two months after the intervention were significant (p<0.05), but in the control group, only the changes in the mean score of performance were significant (p<0.05). Conclusion. The results showed that the HBM-based intervention is effective in promoting nurses’ knowledge, attitude, and performance in preventing nosocomial infections. hence, periodical and in-service HBM-based training programs on preventing nosocomial infections are recommended to be held for nurses.